DAYS on DIFFRACTION 2006 2006
DOI: 10.1109/dd.2006.348175
|View full text |Cite
|
Sign up to set email alerts
|

Coherent states of Krawtchouk oscillator and beyond

Abstract: In the frame of our approach we constructed the generalized oscillator connected with Krawtchouk polynomials (named Krawtchouk oscillator) and coherent states for this oscillator too. . These polynomials provide an important example of the classical orthogonal polynomials of discrete variable. It is very attractive for some applications that they can be considered as finitedimensional approximations of the Hermite and Charlier polynomials [3]. In the papers [6] -[11] the authors proposed a new approach to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this paper, we have studied the different patterns of energy spectrum of the nonlinear f -oscillator associated with the q-deformed Heisenberg-Weyl algebra U (α,β,γ ) q (h 4 ) where, in particular, inequidistant spectra of energy were detected and analysed in details. This fact has motivated the construction of a general class of generalized q-deformed coherent states related to the nonlinear f -oscillator which encompasses a wide class of q-deformed coherent states proposed in the literature [6][7][8][9][10][11][12][13][14][15][16][17]. Next, we have obtained analytical expressions for the scalar product, the completeness relation, the displacement operator, and the time evolution of a small group of q-deformed coherent states defined for q ∈ (0, 1) and restricted to specific values of parameters α and γ , namely α > γ > 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have studied the different patterns of energy spectrum of the nonlinear f -oscillator associated with the q-deformed Heisenberg-Weyl algebra U (α,β,γ ) q (h 4 ) where, in particular, inequidistant spectra of energy were detected and analysed in details. This fact has motivated the construction of a general class of generalized q-deformed coherent states related to the nonlinear f -oscillator which encompasses a wide class of q-deformed coherent states proposed in the literature [6][7][8][9][10][11][12][13][14][15][16][17]. Next, we have obtained analytical expressions for the scalar product, the completeness relation, the displacement operator, and the time evolution of a small group of q-deformed coherent states defined for q ∈ (0, 1) and restricted to specific values of parameters α and γ , namely α > γ > 0.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one of the most common states studied in literature are Klauder's coherent states [5] defined by application of a unitary displacement operator D(z) = exp(za † − z * a) acting on the vacuum state |0 (i.e., |z = D(z)|0 ), with {a, a † , n} satisfying the Heisenberg-Weyl algebra h 4 . Many authors have also investigated the q-deformed coherent states, which are associated with a generalization of the harmonic oscillator commutation relation, in different contexts and predicted new interesting results [6][7][8][9][10][11][12][13][14][15][16][17][18] For instance, Man'ko et al [13] have extended the theory of the usual coherent states to nonlinear coherent states using as examples the deformation relative to the dark states of trapped ions [12]. El Baz and Hassouni [14] have discussed the construction of coherent states associated to deformed bosons oscillators with emphasis on the normalizability, continuity and resolution of unity properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that connection, recently we have shown in Ref. [17] that definite 3-, 4-, and 5-parameter deformed extensions of the p,q-oscillator considered in [18,19,20,21] also belong to the Fibonacci class, i.e., possess the FP. In that same paper, we studied a principally different, socalled µ-deformed oscillator proposed earlier in [22], and shown that it does not possess the FP.…”
Section: Introductionmentioning
confidence: 95%
“…For example, the widely studied harmonic oscillator system has several q-deformed descriptions [4,5]. These are obtained from each other by transformation, as shown in [6,7]. Some of the main problems in obtaining the qoscillator are the spectrum, Hamiltonian, position and time operator.…”
Section: Introductionmentioning
confidence: 99%